Asuhan Keperawatan pada Bayi Baru Lahir dengan Resiko Tinggi Terjadi Infeksi Tali Pusat di RSUD Budhi Asih - Jesika Wirania Nukami; Fitria Prihatini (STIKes Persada Husada Indonesia, 2022)
Neonates are infants aged 0 (newborn) to the age of 1 month old after birth. The umbilical cord is a strap extending from umbilicus to the placental fetal surface. To prevent cord infection, writer will carry out cord care measures. The aim of this study is to observe preventive cord nuring care to avoid infection to the cords. In this study, writer applied qualitative descriptive with intervention method, i.e. a study to provide an overview that occurred in the field. The approach used in this study is a case study of implementing nursing care by providing intervention to the respondents. Participants in this study are two sets of different infants with families, especially infants’ mothers and room nurses. Data collection techniques used are by physical examination, interviews, observation, and patient status and test data validity is by triangulation of data sources. Results from nursing care carried out 3x24hrs period found a diagnose of high risk of infection related to the dissolution of tissue continuity due to umbilical cord cutting, and demonstrated with umbilical cord care in a sterile, clean condition with 70% alcohol is performed after bathing the baby, cord care is performed once daily per day in preventing the occurrence of cord infection. The study case carried out by the writer concluded cord treatment once daily in sterile, clean condition with 70% alcohol can prevent infection. Recommended for next researcher on cord treatment care to be further developed and still using 70% alcohol.